Female identity in the post-millennial Nigerian novel: a study of Adichie, Atta, and Unigwe - Wambui, Mary Theru (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2015)
This thesis project examines the work of three female Nigerian authors: Chimamanda Ngozi Adichie, Sefi Atta and Chika Unigwe. They are part of a growing number of young African writers who are receiving international acclaim and challenging narratives that have long defined the continent in pejorative terms. They question what it means to be female and African in a transcultural, global world but counter discourses that are both restrictive and prescriptive. Their female characters are not imaged in binary terms as either victims or villains. For all three writers, the African story has to be told in its entirety incorporating what some may argue are negative stereotypes but doing so in a manner that examines and undermines those same stereotypes. For the purposes of the thesis, I focus on their first novels: Adichie's Purple Hibiscus, Atta's Everything Good Will Come and Unigwe's On Black Sisters' Street. Chapter One examines Purple Hibiscus and argues that the novel is much more than a coming of age story or, as some critics have posited, an allegory of the postcolonial state. Chapter Two highlights Atta's use of fairly familiar feminist theories but grounds them in the lived realities of the African city. All three authors are concerned with issues of violence and death. Unigwe's novel, which forms the focus of Chapter Three, offers a critical perspective on how both of those themes intersect with the increasing commercialisation of global culture. Her characters are female sex workers whose lives are irrevocably altered by the murder of one of their colleagues. I conclude by arguing that the three novels offer a nuanced if not necessarily new understanding of the various social, economic and political forces that continue to shape the lives of women on the continent.
Keywords: Adichie, Chimamanda Ngozi, 1977- -- Criticism and interpretation; Adichie, Chimamanda Ngozi, 1977-. Purple hibiscus; Atta, Sefi -- Criticism and interpretation; Atta, Sefi -- Everything good will come; Unigwe, Chika. Criticism and interpretation; Unigwe, Chika. Fata Morgana -- English; Nigerian fiction -- History and criticism; Women -- Identity; Women in literature; Feminism in literature